Impact of perceived social support on pain perception in virtual reality - Neumann, Isabel; Käthner, Ivo; Gromer, Daniel; Pauli, Paul (Computers in human behavior, 2023)
Social influences are important modulators of pain. Experimental studies demonstrated analgesic effects of explicit social support. As digital health care gains importance, this study investigated influences of social support by virtual characters and their perceived agency in virtual reality on pain. In a within-subjects design, participants experienced painful heat stimuli in VR. Either a virtual character provided verbal support prior to the pain stimuli or not (support vs. no support condition). In addition, participants were instructed that a real human (avatar condition) or a computer script (virtual agent) controlled the virtual character. However, in both conditions, the virtual character was computer-controlled. Main outcome measures were pain ratings and physiological pain responses. Virtual verbal support affected physiological responses in terms of “stress buffering”, but not pain ratings. The agency manipulation was successful as the avatar yielded higher ratings of perceived human-likeness, helpfulness and realism compared to the virtual agent. However, agency of the character did not affect pain responses. This study revealed that virtual verbal support positively influences physiological pain responses independently of perceived agency. The findings have important clinical implications as virtual interactions and digital health interventions are increasingly relevant for pain treatment. •Participants felt more present in the virtual world with a virtual character.•Social support provided by a virtual character buffered physiological reactions.•Pain ratings were not affected by social support provided of virtual characters.•The perceived agency of the virtual character did not affect pain responses.